A Role for the Retinoblastoma Protein As a Regulator of Mouse Osteoblast Cell Adhesion: Implications for Osteogenesis and Osteosarcoma Formation - Sosa-García, Bernadette; Gunduz, Volkan; Vázquez-Rivera, Viviana; Cress, W. Douglas; Wright, Gabriela; Bian, Haikuo; Hinds, Philip W.; Santiago-Cardona, Pedro G. (PloS one, 2010)
The retinoblastoma protein (pRb) is a cell cycle regulator inactivated in most human cancers. Loss of pRb function results from mutations in the gene coding for pRb or for any of its upstream regulators. Although pRb is predominantly known as a cell cycle repressor, our data point to additional pRb functions in cell adhesion. Our data show that pRb regulates the expression of a wide repertoire of cell adhesion genes and regulates the assembly of the adherens junctions required for cell adhesion. We conducted our studies in osteoblasts, which depend on both pRb and on cell-to-cell contacts for their differentiation and function. We generated knockout mice in which the RB gene was excised specifically in osteoblasts using the cre-lox P system and found that osteoblasts from pRb knockout mice did not assemble adherens junction at their membranes. pRb depletion in wild type osteoblasts using RNAi also disrupted adherens junctions. Microarrays comparing pRb-expressing and pRb-deficient osteoblasts showed that pRb controls the expression of a number of cell adhesion genes, including cadherins. Furthermore, pRb knockout mice showed bone abnormalities consistent with osteoblast adhesion defects. We also found that pRb controls the function of merlin, a well-known regulator of adherens junction assembly, by repressing Rac1 and its effector Pak1. Using qRT-PCR, immunoblots, co-immunoprecipitation assays, and immunofluorescent labeling, we observed that pRb loss resulted in Rac1 and Pak1 overexpression concomitant with merlin inactivation by Pak1, merlin detachment from the membrane, and adherens junction loss. Our data support a pRb function in cell adhesion while elucidating the mechanism for this function. Our work suggests that in some tumor types pRb inactivation results in both a loss of cell cycle control that promotes initial tumor growth as well as in a loss of cell-to-cell contacts, which contributes to later stages of metastasis.